Determinants for positive environmental action of the solid waste management of Guacimo, Costa Rica - Campos-Rodríguez, Rooel (2014)
The aim of this paper is to show the results of a study on knowledge, attitudes and barriers to implement a comprehensive solid waste management program (SWMP) in the canton of Guácimo, Limón, Costa Rica. The municipality, as the governing institution of the county, does not possess a study of this nature, so this research will be a starting point to gather baseline information and move towards the SWMP. In order to achieve the objective, two surveys were created, validated and applied to the municipal council; the selected neighborhoods according to their income levels, according to the regulations of composition studies in the country, and selected businesses ranked according to their activities as classified in the ISIC (International Standard Industrial Code). In all cases statistical tools for the sample selection and data comparison were applied. Once data was collected, it was systematized and organized in attributes such as knowledge, attitudes, behaviors, values and barriers to SWMP in Guácimo. There is a public dissatisfaction on Guácimo municipal actions in terms of a SWMP, while there is a clear commitment from the same city council and other social actors to route the canton towards sustaina-ble development, involving correct use, proper treatment and disposal of municipal solid waste. It is expected that the information obtained in this research will help the municipality of Guácimo to take sustainable decisions involving the community in a collaborative effort to properly manage solid waste in the Canton.